Radiology in pleural disease: state of the art. - Evans, A; Gleeson, F (2004)
Diseases of the pleura and pleural space are common and present a significant contribution to the workload of the chest radiologist. The radiology department plays a crucial role in the imaging and management of pleural disease. This review aims to describe and illustrate the appearances of common pleural pathologies on various radiological modalities including plain film, ultrasound, CT, magnetic resonance imaging and positron emission tomography. The review will also address the state-of-the-art techniques used to image pleural disease and discuss image-guided intervention in the management of pleural disease.